Specifying social cognitive processes with a social dual-task paradigm - Liepelt, Roman; Stenzel, Anna; Lappe, Markus (Frontiers in Human Neuroscience, 2012)
Automatic imitation tasks measuring motor priming effects showed that we directly map observed actions of other agents onto our own motor repertoire (direct matching). A recent joint-action study using a social dual-task paradigm provided evidence for task monitoring. In the present study, we aimed to test a) if automatic imitation is disturbed during joint action and b) if task monitoring is content or time dependent. We used a social dual task that was made of an automatic imitation task (Person 1: Task 1) and a two-choice number task (Person 2: Task 2). Each participant performed one of the two tasks, which were given with a variable stimulus onset asynchrony (SOA), in an individual and a joint condition. We found a regular motor priming effect in individual and joint conditions. Under joint conditions, we replicated the previous finding of an increase of reaction times for Person 2 with decreasing SOA. The latter effect was not related to the specific responses performed by both persons. Further, we did not find evidence for a representation of the other’s specific S-R mappings. Our findings suggest that a) automatic imitation is not disturbed during joint action and b) task monitoring is time dependent.